Biodegradable and pH-responsive piperazine-based aliphatic polyesters with tunable hydrophilicity. (5th January 2022) - Goel, Shubhra; Dubey, Shubham; Sharma, Shilpi; Jacob, Josemon
Graphical abstract: Highlights: Piperazine based novel polyesters were prepared using different alkanediols. At pH 1.0, the polyester became more hydrophilic and was readily soluble in water. Hydrolytic degradation shows ∼23–50% decrease in molecular weight at neutral pH. Charge introduction improves the polymer hydrophilicity and the biodegradability. Abstract: In this article, we report on a new class of biodegradable piperazine-based aliphatic pH-responsive polyesters with tunable hydrophilicity. The aliphatic polyesters PC1-PC4 with high thermal stability up to 340 °C were synthesized by polycondensation of dimethyl 2, 2′-(piperazin-1, 4-diyl)diacetate with a series of alkane diols (C4 to C10). The resulting polyesters are found to be highly crystalline with ∼47–55% crystallinity as estimated from XRD and moderately hydrophilic as the water contact angle was found to be in the range of 63°–72°. An N-alkylation or protonation approach was used to tune their crystallinity and hydrophilicity so as to enhance biodegradability. Upon quaternization with methyl iodide, a significant effect on functional and structural properties was observed with reduced crystallinity and enhanced hydrophilicity, as the contact angle decreased down to 24° upon methylation. The pH-responsive nature of the material was evaluated with zeta potential measurements, and the surface charge increased up to +41.4 mV with a more positive charge on the polymer backbone at pH 2 for polyester PC2. Further, microbial and hydrolytic degradation studies showed that the quaternized polyesters PC6 and PC9 exhibit faster degradation when compared to their parent polymer PC2, demonstrating their significance as a new class of biodegradable polyesters.